RANCANGAN SISTEM INFORMASI PADA USAHA PENGKAPAN IKAN KOMODITAS UNGGULAN ( Study Kasus Ikan Tuna (Thunus Sp) ) DI PELABUHAN PERIKANAN SAMUDRA CILACAP - Adhitya, Ega; Rosyid, Abdul; Boesono, Herry (Journal of Fisheries Resources Utilization Management and Technology, 2012)
Data and information is very important to make a decision however, the limitations of the tuna fishery emerged information technology issues such as information required in the tuna fishery stakeholders Cilacap PPS. his study aims to Know the potential of fishery resources landed in PPS Cilacap, Designing information systems tuna fisheries (Thunus sp) in digital form and make it easier stakeholder in case of input and fisheries output in the PPSC This study applied a systems approach, a method that consider information systems as a whole integration for each activity or application. The system is limited to only about the development of tuna fisheries in PPS Cilacap. The technology used for data processing and information tuna fishery is a computerized information technology. The demand of analysis system obtained from the parties involved, namely the PPSC, Fisheries, Fishers and stakeholders. Manufacturing information system of tuna fishing design in the PPS Cilacap starting from the input data is Cilacap PPS profile information data, tuna information and tuna fisheries statistical information, which will be created in a digital information system with media Internet-web MY SQL with SIUPIT name (SISTEM INFORMASI USAHA PENANGKAPAN IKAN TUNA ) SIUPIT is computerized information system that can be used to assist and facilitate data and information services businesses in the tuna fishery PPS Cilacap for stakeholders, such as accelerating time information services, minimize mistakes and get the highest reporting of data in a shorter time and accurate.